(untitled) (TEL Tempo, Espaço e Linguagem, 2012)
A leitura de relatos do início dos oitocentos nos oferecem panoramas analíticos mais complexos das supostas causas da “ruína” em que se encontrava a Capitania do Ceará, além de permitir caracterizar, com esta variedade de opiniões, quais eram os rumos que deveriam ser tomados pelo governo lusitano para civilizar o Ceará. Land in ruins: poverty, violence and power in Ceará in early nineteenth century reports Abstract: The reading of accounts of the early eighteen hundreds offers us more complex analytical panoramas of the supposed causes of the "ruin" in which one encountered the Capitania of Ceará, besides allowing us to characterize, with a variety of opinions, which were the directions that should be taken by the Portuguese government to civilize Ceará. Keywords: indigenous history, history of indigenization, history of Ceará Tierra en ruinas: la pobreza, la violencia y el poder en Ceará en los informes del siglo XIX Resúmen: La lectura de los relatos del principio del siglo XIX nos ofrecen descripciones analíticas más complejas de las presuntas causas de la "ruina" en la que estaba la Capitanía del Ceará, además de permitir caracterizar, con esta variedad de opiniones, cuáles eran las instrucciones que se deberían tomar por parte del gobierno lusitano para civilizar el Ceará. Palabras clave: historia indígena, la historia de indigenización, historia de Ceará